Socialization on Making Infiltration Wells in Halaban Village, Besitang District, Langkat Regency - Wiwin Nurzanah; Indrayani; Irma Dewi (Universitas Lancang Kuning, 2023)
Halaban Village is located in Besitang District, Langkat Regency. This village does not have clean water supply facilities, either government or private water treatment plants. This is why the majority of villagers use groundwater for their daily needs. But the groundwater will dry up when the dry season comes. This condition is a problem that has not been resolved until now. The community has to spend quite a lot of money to buy clean water for their daily needs when the dry season comes. This problem encourages the author to help the community by providing appropriate technological knowledge regarding the meaning and benefits of infiltration wells. This media is one way to overcome the problem of water shortages. The method used is a non-formal socialization method so that the knowledge conveyed can be better understood by the community. The results of this socialization are expected to be followed by the construction of infiltration wells in every Halaban village house.